PENGARUH PENGUNGKAPAN AUDIT INTERNAL TERHADAP BIAYA AUDIT - Widiar, RR. Wulan Indri; Faisal, Faisal (APSSAI, 2023)
This study examines the content of internal audit disclosures and their effect on audit fees. The sample consisted of 188 public companies listed on the Indonesia Stock Exchange in 2018. The analysis techniques used include content analysis, descriptive analysis, and multiple regression analysis. The results showed that the mean disclosure of internal audit information is 56.99%. Information related to the existence of internal audit and internal audit structure are the items most disclosed by the entire company. Mean disclosures by sector show that property, real estate, and building construction are the most disclosed sectors (60.93%). The results of the regression analysis show that internal audit disclosure has no effect on audit fees. However, if the disclosures are grouped under general and specific disclosures, specific internal audit disclosures have a negative effect on audit fees. As a result of these findings, specific internal audit disclosures may indicate that the firm being effectively monitored and controlled may be influencing audit fees.